2010
DOI: 10.1186/1477-7525-8-100
|View full text |Cite
|
Sign up to set email alerts
|

Personality and the physician-patient relationship as predictors of quality of life of cardiac patients after rehabilitation

Abstract: BackgroundNumerous studies document the influence of psychosocial variables on the course of coronary heart disease. This study examines the influence of personality traits (trait anger, cynicism) and aspects of the physician-patient relationship (promoting patient participation by the physician, active communication behavior of the patient, trust in the physician) on the health related quality of life (HRQOL) of cardiac patients after rehabilitation.MethodsN = 331 patients with chronic ischemic heart disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 65 publications
1
18
0
1
Order By: Relevance
“…There appears to be sufficient evidence that socioeconomic status (SES), as measured by education, income and occupation, is a major predictive factor of HRQoL . Farin and Meder found that individuals with higher SES generally reported higher HRQoL and better health outcomes when compared with individuals with lower SES.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be sufficient evidence that socioeconomic status (SES), as measured by education, income and occupation, is a major predictive factor of HRQoL . Farin and Meder found that individuals with higher SES generally reported higher HRQoL and better health outcomes when compared with individuals with lower SES.…”
Section: Resultsmentioning
confidence: 99%
“…There appears to be sufficient evidence that socioeconomic status (SES), as measured by education, income and occupation, is a major predictive factor of HRQoL . Farin and Meder found that individuals with higher SES generally reported higher HRQoL and better health outcomes when compared with individuals with lower SES. Such a phenomenon is probably due to the increased accessibility and affordability of health‐care services for higher‐SES individuals, which ultimately improves their health outcomes .…”
Section: Resultsmentioning
confidence: 99%
“…The positive association between better physician-patient relationship and patients’ health related quality of life has been reported in many domains of health including HIV/AIDS (Beach, Keruly, & Moore, 2006; Farin & Meder, 2010; Farin & Nagl, 2012; Preau et al, 2004; Shanafelt et al, 2009). However, it seems that this key component of patient care was not fully utilized in China.…”
Section: Discussionmentioning
confidence: 97%
“…Die Berücksichtigung von Patientenpräferen-zen erleichtert dem Behandler die Erfüllung der kommunikationsbezogenen Wünsche und somit die Herstellung eines kongruenten Gesprächsklimas, von dem angenommen wird, dass es in positivem Zusammenhang mit dem Behandlungserfolg steht (erste Ergebnisse in [12]). Farin u. Meder [8], Farin et al [10] sowie Farin u. Nagl (eingereichte Arbeit, [9]) zeigen außerdem, dass bei chronisch Kranken in der Rehabilitation die Patient-Behandler-Beziehung bedeutsamen Einfluss auf Verbesserungen der Lebensqualität nach der Rehabilitation besitzt.…”
Section: Diskussionunclassified